Water vapor absorption line intensities in the 1900–6600 cm-1 region; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 109, № 16 - Mikhailenko S. N. Semen Nikolaevich; Keppler Alber K. A.; Mellau G.; Klee S.; Winnewisser B. P.; Winnewisser M.; Tyuterev Vl. G. (2008, 2008)
Title screen